Raising Awareness of Drug Abuse Dangers Among Santri: A Community Service Program at Pesantren Ihyaussunnah, Lhokseumawe - T Saifullah (Yayasan Daarul Huda Kruengmane, 2026)
Drug abuse is one of the serious problems that threatens the younger generation, including students (santri) in Islamic boarding school environments. Although Islamic boarding schools are known as educational institutions based on religious and moral values, the potential exposure to drugs remains present along with social development and advances in information technology. This community service activity aims to increase students’ understanding and awareness of the dangers of drugs through a socialization program conducted at Pesantren Ihyaussunnah with 50 participating students. The implementation methods included counseling sessions, interactive discussions, educational media presentations, and evaluation of participants’ understanding through question-and-answer sessions and reflection. The results of the activity indicate an increase in students’ knowledge regarding the types of drugs, the negative impacts of drug abuse on health, social life, and religious values, as well as efforts to prevent drug abuse in daily life. This activity is expected to serve as a preventive measure in protecting students from the dangers of drugs and to strengthen the role of Islamic boarding schools as educational institutions that actively contribute to the prevention of drug abuse.